If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + 3) + 7m = 3(m + -9) Reorder the terms: 5(3 + m) + 7m = 3(m + -9) (3 * 5 + m * 5) + 7m = 3(m + -9) (15 + 5m) + 7m = 3(m + -9) Combine like terms: 5m + 7m = 12m 15 + 12m = 3(m + -9) Reorder the terms: 15 + 12m = 3(-9 + m) 15 + 12m = (-9 * 3 + m * 3) 15 + 12m = (-27 + 3m) Solving 15 + 12m = -27 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 15 + 12m + -3m = -27 + 3m + -3m Combine like terms: 12m + -3m = 9m 15 + 9m = -27 + 3m + -3m Combine like terms: 3m + -3m = 0 15 + 9m = -27 + 0 15 + 9m = -27 Add '-15' to each side of the equation. 15 + -15 + 9m = -27 + -15 Combine like terms: 15 + -15 = 0 0 + 9m = -27 + -15 9m = -27 + -15 Combine like terms: -27 + -15 = -42 9m = -42 Divide each side by '9'. m = -4.666666667 Simplifying m = -4.666666667
| 5(-7x+2)=-40 | | 3(3n+40)=54+6n | | 24=8c | | -3x-15=9x+9 | | m+4=1 | | 2x^2+3-5=0 | | 6p=-96 | | n/8=-12 | | 30=12n-18 | | -5+n=-23 | | -632=4g | | -9j-10=62 | | 8=-12+x | | 2=4h-14 | | 5w-3w= | | -6=v-4 | | 6x+8=2x-28 | | 18+5.50x=y | | J+434=-376 | | (-4x-5)=-125 | | Y=(x^2+5)2x+1 | | 2x^2+5x+15=0 | | 49=16+3j | | -10=x-17 | | -7-5(8n*8)=193 | | 6=d/7 | | -2x=-26 | | 4x^2+3x-76=0 | | 9+5.50x=y | | -3h-4.2=55-11h | | n-16=-8 | | 15+2h=9 |